Beclomethasone dipropionate aerosol in treatment of perennial allergic rhinitis in children. - Shore, S C (1977)
Forty-four children with perennial allergic rhinitis who had failed to respond to conventional therapy, including sodium cromoglycate insufflation and hyposensitization, were treated with beclomethasone aerosol given intranasally. The study was conducted in a double-blind manner, the patients being allocated active drug or placebo for a 3-week period, followed by a 1-week rest period. The treatments were then crossed over for a period of 3 weeks. After this all children were put on active drug and followed-up at monthly intervals for a period of 3 months. Results were graded as either success of failure, and success had to be an unequivocal vote for the active drug by the patient, parent, and doctor. An overall success rate of 77% was obtained and no untoward or toxic effect was noted in any child. Tetracosactrin tests in 5 children remained normal at the end of the study period. We found intranasal beclomethasone dipropionate to be the most effective drug we have used for treating perennial allergic rhinitis in children.